2018
DOI: 10.1101/255091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Causal explanation of individual differences in human sensorimotor memory formation

Abstract: Sensorimotor cortex mediates the formation of adaptation memory. Individuals differ in the rate at which they acquire, retain, and generalize adaptation. We present a mechanistic explanation of the neurochemical and computational causes of this variation in humans. Neuroimaging identified structural, functional and neurochemical covariates of a computational parameter that determines memory persistence. To establish causality, we increased sensorimotor cortex excitability during adaptation, using transcranial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 117 publications
(160 reference statements)
1
12
1
Order By: Relevance
“…Although long-term retention increased numerically, this was not significant (t (2235) = −1.35, p = 0.18; Table S8 -model 4). The lack of a significant memory gain from stimulation across the group contrasts with our previous findings in young adults 47,48 .…”
Section: -Minutes 24-hourscontrasting
confidence: 99%
“…Although long-term retention increased numerically, this was not significant (t (2235) = −1.35, p = 0.18; Table S8 -model 4). The lack of a significant memory gain from stimulation across the group contrasts with our previous findings in young adults 47,48 .…”
Section: -Minutes 24-hourscontrasting
confidence: 99%
“…Error in the PM session, where no perturbation was present, measured the degree to which participants unlearnt the mapping and retained the visuomotor aftereffect. Previous studies have shown that higher GABA concentrations correlate with decreased visuomotor aftereffect and decreased retention of the learnt mapping when tested on the same task later (O'Shea et al 2017;Petitet et al 2018).…”
Section: Motor Tasksmentioning
confidence: 96%
“…Studies in healthy individuals have identified changes in motor cortex inhibition as a key physiological feature of motor learning, with decreases in concentration of the inhibitory neurotransmitter GABA being observed during motor learning (Floyer-Lea et al 2006;Kolasinski et al 2018) and motor plasticity (Bachtiar et al 2018;Stagg et al 2009;Stagg et al 2011). Furthermore, interventions that decrease M1 GABA concentration [GABA] (Stagg et al 2011(Stagg et al , 2009a) also tend to improve performance on sequence learning tasks (Buch et al 2017;Nitsche et al 2003) and increase retention of visuomotor prism adaptation (O'Shea et al 2017;Petitet et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptation is well-described by state space models that account for behaviour as the output of two or more parallel learning systems operating on different timescales, fast and slow (Smith et al, 2006, Kording et al, 2007, Joiner and Smith, 2008, Kim et al, 2015. We developed a state space model variant that captured the gradually changing magnitude and stability of the prism after effect during adaptation (Petitet et al, 2018). We used this to identify functional brain signals whose timecourse correlated with the fast and 3 slow learning dynamics that underpin the formation of the behavioural after effect.…”
Section: Introductionmentioning
confidence: 99%
“…Healthy individuals and stroke patients performed prism adaptation during fMRI (Bultitude et al, 2016). Using a similar approach to Kim et al (2015), a computational model was fitted to prism adaptation behaviour to extract time-varying regressors of brain activity that follow a fast or slow time-scale (Petitet et al, 2018). In both healthy individuals and stroke patients, functional signal in left sensorimotor cortex correlated with the slow timescale dynamics, indicating that this brain region mediates the formation of the prism after effect.…”
Section: Introductionmentioning
confidence: 99%